The Influence Of Financial Literacy On The Financial Management Of Umkm South Bontonompo District, Gowa Regency - Nur Resky Amriani; Muhammad Nur Abdi; firman Syah (International Journal of Economic Research and Financial Accounting, 2024)
This type of research uses a descriptive method with a quantitative approach, which aims to determine the influence of financial literacy on financial management of MSMEs in South Bontonompo District, Gowa Regency. This research was carried out in South Bontonompo District, Gowa Regency, which took place from 7 May 2024 to 7 July 2024. The sample used in this research was 75 MSME actors in South Bontonompo District, Gowa Regency. Data collection is carried out by distributing questionnaires or questionnaires. Furthermore, the data obtained was then processed using a simple linear regression data analysis method and processed using the Statistical Package For The Social Science SPSS Version 23 application. The research results showed that financial literacy (X) was obtained by t-count 11,929 > t-table 1.666 and the sig value is 0.000<0.05, thus the financial literacy variable has a positive and significant effect on the financial management variable. So the results of hypothesis testing show that H1: Financial Literacy has a positive and significant influence on the financial management of MSMEs in South Bontonompo District, Gowa Regency, is accepted.